Hearing the mermaid's song : the Umbanda religion in Rio de Janeiro - Hale, Lindsay (Albuquerque, [N.M.] : University of New Mexico Press, 2009)
"The Umbanda religion summons the spirits of old slaves and Brazilian Indians to speak through the mouths of mediums in trance. Its practitioners worship African gods, often calling them by the names of Catholic saints; simultaneously embrace the concepts of karma, reincarnation, and Christian charity; and believe in the capacities of both modern science and ancient magic. A relatively new religion dating to the beginning of the twentieth century, Umbanda has its origins in Rio de Janeiro and its surrounding urban areas where Afro-Brazilians, many ex-slaves or the descendants of slaves, practiced versions of the religion handed down to them by their ancestors. Umbanda's popularity has grown tremendously over the past century, attracting not only those who seek the assistance of spirits in solving problems in their lives, but those in pursuit of a path to a rich spiritual life and a fellowship of faith and service." "Over the course of nearly a decade, Lindsay Hale spent countless hours attending rituals and festivals and interviewing participants of Umbanda, immersing himself in this fascinating religious world. In describing its many aspects and exploring its unique place within the lives of a wide variety of practitioners, Hale places Umbanda spiritual beliefs and practices within the broader context of Brazilian history and culture."--BOOK JACKET.
Includes bibliographical references (pages 176-184) and index.
Description based on print version record.
Keywords: Umbanda (Cult) -- Brazil -- Rio de Janeiro; Spirit possession -- Brazil -- Rio de Janeiro; Rio de Janeiro (Brazil) -- Religious life and customs; Rio de Janeiro (Brazil) -- Social life and customs; BODY, MIND & SPIRIT / Spirituality / Paganism & Neo-Paganism; RELIGION / Comparative Religion; Electronic books